DIAGNOSTIC AND MANAGEMENT OF AUTISM - Riandewi Griadhi, Made Ovy; Ratep, Nyoman; Westa, Wayan (E-Jurnal Medika Udayana, 2013)
Normal 0 false false false EN-US X-NONE X-NONE Autism is a coalition condition of development disorders which the clinical symptoms are social interaction difficulty, verbal and nonverbal communication problem, repetition of behavior and actions, and shallow and obsessive of interest. Autism is caused by some kind of factors. Genetic and environment factors are thought have a significant role. For diagnosing autism need a kind of criterions from DSM IV, or screening by CARS rating system ( Childhood Autism Rating Scale ), Checklist for Autism in Toddlers (CHAT), and Autism Screening Questionnaire . Management of autism must be holistic consist of medication and non medication. The aim of therapy for autism is reducing behavior problems and increasing studying ability especially in language mastery. The autism that screened earlier then got a directly treatment can live independently but still depend on the type of autistic disorders and the age at that time. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: autism, interaction problems, communication problems, repetition of behavior, obsessive interest